1995
DOI: 10.1002/ijc.2910620504
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma pepsinogen levels in a population at high risk for stomach cancer in venezuela

Abstract: Determinants of plasma pepsinogens (PG) levels were studied in 1365 participants in a chemoprevention trial for gastric pre-cancerous lesions being conducted in Venezuela. Gastric biopsies, plasma samples and information on smoking and dietary habits were obtained at baseline examination. Both PG-I and PG-II levels increased progressively with the level of Helicobacter pylori infection in gastric biopsies, resulting in no clear trend in the I/II ratio. Instead, there was a progressive decrease in the I/II rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Although several previous studies reported the significant relations of lifestyle to the risk of H. pylori infection and/or CAG, other studies have not reported such relations, and findings are inconsistent [5][6][7][14][15][16][27][28][29][30][31][32][33][34][35][36][37]. There are no studies reporting the significant relationship between green tea consumption and the risk of H. pylori infection or CAG.…”
Section: Discussionmentioning
confidence: 99%
“…Although several previous studies reported the significant relations of lifestyle to the risk of H. pylori infection and/or CAG, other studies have not reported such relations, and findings are inconsistent [5][6][7][14][15][16][27][28][29][30][31][32][33][34][35][36][37]. There are no studies reporting the significant relationship between green tea consumption and the risk of H. pylori infection or CAG.…”
Section: Discussionmentioning
confidence: 99%
“…The study population was drawn from the participants of a double-blind chemoprevention trial aimed at assessing the effect of anti-oxidant vitamins on the progression of gastric pre-cancerous lesions, in the framework of the Gastric Cancer Control Program of Tachira State, Venezuela (Kato et al, 1995). Eligible subjects were permanent residents of the state of Tachira, between 35 and 69 years of age, who, after double-contrast X-ray, were selected to undergo gastroscopic examination.…”
Section: Methodsmentioning
confidence: 99%
“…Caution should be used in generalizing these results to other populations as the study subjects were derived from participants in a gastric cancer screening program (Kato et al, 1995), and gastric symptoms represented a possible reason for participating in this program. In addition, most of the adult population in high-risk areas for stomach cancer had some type of gastric pre-cancerous lesion, such as superficial gastritis, chronic gastritis, chronic atrophic gastritis or intestinal metaplasia (Correa et al, 1970).…”
Section: Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal cut-off points of PGI and/or PGI/PGII for the detection of precancerous lesions and gastric cancer may vary between populations [9,24,[26][27][28][29][30][31]. This may be due to genetic differences, prevalence and characteristics of infection with H. pylori or other micro-organisms, lifestyle factors and also the local definition of atrophy and the diagnostic methods used.…”
Section: Discussionmentioning
confidence: 99%